Social network interventions for health behaviour change: a systematic review. (November 2017) - Hunter, Ruth F; de la Haye, Kayla; Badham, Jennifer; Valente, Tom; Clarke, Mike; Kee, Frank
Abstract: Background: We are all embedded in social networks, and evidence demonstrates that our embeddedness in these networks has a substantial impact on our health behaviours. However, we know little about how to harness them in health behaviour change interventions. The aim of this study was to investigate the effects of social network interventions for health behaviour change. Methods: Eight databases (Medline, EMBASE, Web of Knowledge, Scopus, PsycINFO, ERIC, IBSS, and Sociological Abstracts were searched independently by two reviewers for articles published in English between Jan 1, 2000, and March 1, 2017. Eligibility criteria included a social network intervention for health behaviour change, a primary outcome measure of health behaviour change, and a comparator group. Evidence was synthesised by the network intervention approach based on a predefined taxonomy (Individual—using network data to identify certain individuals; Segmentation—directed towards groups of people clustered in a network; Induction—activation of existing social ties to diffuse healthy behaviours; Alteration—changing the structure of the network by the addition of new members or breaking existing ties. Studies were described as providing strong evidence if at least 80% of included studies demonstrated a significant intervention effect (p<0·05 vs control). Findings: Of the 23 234 publications identified, 39 were included. Overall, there was strong evidence for a significant intervention effect (82%, 32 of 39 studies) and maintained intervention effect (88%, 29/33) for social network interventions. There was strong evidence demonstrating a significant intervention effect and maintained intervention effect for the Individuals (8/8 studies), Segmentation (5/5), and Alteration (3/3) network approaches, and promising evidence to support an intervention effect (68%, 15/22) for Induction approaches. Interpretation: This review provides strong evidence of the effectiveness of social network interventions for health behaviour change and maintenance. Most existing interventions continue to focus on individual-level behaviour and fail to address the influential role of individuals' social systems and environments. There has been a parallel and growing interest in understanding the effects of social networks on health-related behaviour and the reframing of non-communicable conditions as being socially transmitted; a particular backdrop to this has been the emerging prominence of complexity science public health. Funding: RH is funded by a Career Development Fellowship from the National Institute for Health Research.